Multi-Component Herbal Products in the Prevention and Treatment of Chemotherapy-Associated Toxicity and Side Effects: A Review on Experimental and Clinical Evidences - Fu, Bowen; Wang, Ning; Tan, Hor-Yue; Li, Sha; Cheung, Fan; Feng, Yibin (Frontiers in Pharmacology, 2018)
Chemotherapy is nowadays the main treatment of human cancers. Chemotherapeutic agents target rapidly dividing cancer cells to suppress tumor progression, however, their non-specific cytotoxicity often leads to significant side effects that might be intolerable to cancer patients. Multi-component herbal products have been used for thousands of years for the treatment of multiple human diseases. This study aims to systematically summarize and evaluate the experimental and clinical evidences of the efficacy of multi-component herbal products in improving chemotherapy-induced side effect. Literature was retrieved from PubMed database and evaluated based on the side effects described. Multi-component herbal products were found to be effective in ameliorating the neurotoxicity, gastrointestinal toxicity, hematological toxicity, cardiotoxicity, hepatotoxicity and nephrotoxicity. Both experimental and clinical evidences were found, indicating the potential of applying multicomponent herbal products in the clinical treatment of chemotherapy-induced side effects. However, the lack of mechanistic and pharmacokinetic studies, inconsistency in product quality, as well as insufficient clinical evidence suggested that more investigations are urgently necessary. In all, our review shed light on the potential of using multi-component herbal products in the clinical management of chemotherapy-induced toxicity and side effects.